The Design of a 'Two-Pillar' Monetary Policy Strategy - Meixing Dai (Kiel Institute for the World Economy (IfW), 2009)
In this paper, it is argued that money supply in a narrow sense and repo interest rate are two independent monetary policy instruments when the effect of interest rate policy cannot be efficiently transmitted to the economy through the monetary and financial markets. In this case, the control of money supply is necessary to reduce the discrepancy between the repo interest rate and the interest rates at which private agents lend and borrow. Using a simple macro-economic model, this study shows how a twopillar monetary policy strategy as practiced by the European central bank (ECB) can be conceived to guarantee macroeconomic stability and the credibility of monetary policy. This strategy can be interpreted as a combination of inflation targeting and monetary targeting. Well conceived monetary targeting with a commitment to a long-run money growth rate corresponding to inflation target could reinforce the credibility of central bank announcements and the role of inflation target as strong and credible nominal anchor for private inflation expectations. However, an inflation-targeting regime associated with Friedman's money supply rule can generate dynamic instability in output, inflation and money demand. Three feedback monetary targeting rules, of which the design depends on economic structure and central bank preferences, are discussed relative to their capability of warranting macroeconomic stability.
Keywords: 330; Two-pillar monetary policy strategy; inflation targeting; monetary targeting; macroeconomic stability; Friedman's k-percent rule; Geldpolitisches Ziel; Inflation Targeting; Geldmengensteuerung; Konjunkturpolitik; Europäische Wirtschafts- und Währungsunion; Theorie; EU-Staaten